BIOSORPTION OF CHROMIUM (VI) BY A MUTATED STRAIN OF Bacillus cereus M116 - Subham Paul; Debabrata Bera; Lalitagauri Ray (Journal of Hazardous Substance Research, 2007)
The removal of chromium, a highly toxic metal causing environmental pollution from dilute aqueous solution, was studied in the present work using growing and washed cells of a mutant strain of Bacillus cereus (M116) isolated from tannery waste. Particularly, the effects of pH, temperature, metal ion concentration and contact time on removal of chromium werestudied. About 40% chromium removal, was observed by growing cells of the selected strain at pH 6.5, temperature 30o±1oC, inoculum size 3%, medium volume 50 ml/250 ml Erlenmeyer flask, and initial chromium concentration 50 ppm. Usingresting cells 98.02% and 78.34% chromium removal was possible with initial chromium concentration of 25 and 50 ppm, respectively, at pH 3.0, temperature 25-35oC and 2.73 g/L biomass concentration. It was found that the overall adsorption process was best described by pseudo-second order kinetics. Freundlich and Langmuir adsorption models were found suitablefor describing the short-term biosorption of chromium (VI). IR spectral analysis of the biomass was carried out to find out the functional groups responsible for chromium (VI) biosorption.
Keywords: lead biosorption; immobilization; pseudo second order; Freundlich isotherm